Examining School Based Health Service Utilization Among Marginalized Youth in Connecticut During COVID - April Joy Damian PhD, MSc, CHPM, PMP; May Oo MPH (SAGE Publishing, 2022)
Purpose This study examines how the coronavirus disease 2019 (COVID-19) is affecting utilization of medical and behavioral health services through school based health centers (SBHC s). Methods We leveraged the electronic health records from one of the largest sponsors of SBHCs in the country, and tested differences in SBHC utilization with chi-square tests one year prior to the pandemic (pre-pandemic: March 2019-February 2020) compared to one year into the pandemic period (March 2020-February 2021). Results A significant difference in SBHC utilization was found between pre-pandemic and pandemic periods (P <.001). 63.5% of SBHC patients accessed medical services pre-pandemic compared to 51.2% during the pandemic. In contrast, 36.5% of SBHC patients accessed behavioral services pre-pandemic compared to 48.8% during the pandemic, representing a 12.3% increase in SBHC behavioral service utilization since the pandemic. Conclusions SBHCs may serve as an invaluable means of ensuring youth, particularly those from disadvantaged communities, have access to needed behavioral health services during the current public health crisis.